POLITENESS STRATEGIES USED BY THE MAIN CHARACTER IN A LETTER TO JULIET MOVIE - Sri Ayu Hidayati; Meisuri Meisuri (LINGUISTICA, 2014)
ABSTRACT The study deals with the types of politeness strategies used by the main character in a letter to Juliet movie. The objectives of study are to find out type of politeness strategies used by the main character in a letter to Juliet movie, to derive the dominant type of politeness strategy that is produced by the main character in a letter to Juliet movie and to elaborate the context of politeness strategies used by the main character in a letter to Juliet movie. The data are dialogue of the main character in a letter to Juliet movie. This research is conducted by using descriptive qualitative design and only focused on the main character. The research findings are positive and negative politeness strategies. There are fifteen strategies of positive politeness and twelve strategies of negative politeness in a letter to Juliet movie. The most dominant politeness strategy uttered by the main character in a letter to Juliet movie was positive politeness strategy. Among them is intensify interest to hearer is dominant type of positive politeness strategy. This type of politeness strategy occurred since character mostly just shared about her experience and inform to other.   Keywords: Politeness strategies, positive politeness strategies, negative politeness strategies